The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ctr.13635
|View full text |Cite
|
Sign up to set email alerts
|

Does intra‐operative verapamil administration in kidney transplantation improve graft function

Abstract: The role of the calcium channel blocker (verapamil) in kidney transplant is controversial. Verapamil has been hypothesized to mitigate ischemia reperfusion injury (IRI) to the allograft. Herein, we evaluated the effect of intra-operative verapamil administration in a large cohort of kidney transplants. Total 684 transplants were performed during 2007-2017. Of these, 348 (50.9%) transplants received verapamil (2.5 mg) Ver (+), and 336 (49.1%) did not, Ver (−). Based on the donor type, the study was divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“… 16 , 18 A more recent single-center study failed to demonstrate that intraoperative verapamil reduced DGF. 21 However, this latter study did observe that only 60% of the DCD Ver (+) group had DGF, in contrast to 80% in the DCD Ver (–) group. 21 Unfortunately, the small sample size and short CIT in the DCD groups limited the generalizability of this conclusion.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“… 16 , 18 A more recent single-center study failed to demonstrate that intraoperative verapamil reduced DGF. 21 However, this latter study did observe that only 60% of the DCD Ver (+) group had DGF, in contrast to 80% in the DCD Ver (–) group. 21 Unfortunately, the small sample size and short CIT in the DCD groups limited the generalizability of this conclusion.…”
Section: Introductionmentioning
confidence: 73%
“…A larger contemporaneous series comprised mainly living donor (39%) and DBD (58%) transplants failed to demonstrate a significant benefit with the use intraoperative verapamil. 21 In the latter report, the small DCD Ver (+) subgroup did have a lower incidence of DGF that did not achieve statistical significance because of sample size limitations. 21 Our single-center matched cohort study included a large Ver (+) DCD cohort (n = 27); however, we also did not demonstrate a significant reduction in DGF versus the Ver (–) DCD cohort.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Their cohort included living donors, brain dead donors, and donation after circulatory death donors, and administration did not improve graft function after transplant in any group. 3 A 2008 study that evaluated the effects of Verapamil on recipients, that had their donated grafts flushed with a preservation solution prior to transplant, found that the addition of Verapamil can improve long-term graft function. 4 This study had limitations noted including the fact that it was not designed with a paired kidney framework.…”
Section: Introductionmentioning
confidence: 99%